(untitled) (Research, Society and Development, 2020)
The coffee growing in Minas Gerais has been outstanding due to the high quality in the production and the cultivar choice is very important during the culture implantation process. Genetic dissimilarity studies are very important to make further advances in breeding programs to obtain more adapted cultivars. Thus, the objective of this work was to evaluate the agronomic potential and genetic dissimilarity among coffee cultivars based on hierarchical and optimization methods. The experiment was installed at the Federal University of Uberlândia, Campus - Monte Carmelo. The planting was carried out in December 2015, using a randomized block design with four replications. A spacing of 3.5 m between rows and 0.6 m between plants was adopted. The treatments consisted of the Coffea arabica cultivars: Acaiá Cerrado - MG 1474; Mundo Novo IAC 379-19; Bourbon Amarelo IAC J10; Catuaí Vermelho IAC 99; Topázio MG 1190; Acauã Novo and IAC 125 RN. Growth, crop yield and physical classification were evaluated for type, size and shape of coffee beans. There was consistency between hierarchical and optimization methods in the groups formation. The cultivar Mundo Novo IAC 379-19 showed the highest vegetative vigor. The cultivar Acaiá Cerrado MG 1474 was the one that obtained the highest yield in the first crop. The cultivar Topázio MG 1190 showed higher genetic dissimilarity compared to the other cultivars. UPGMA multivariate analysis and Tocher optimization methods indicated that the cultivars have genetic variability for the region under study.